Kota Salatiga Menuju Kota Gastronomi - Hendayana Hendayana (Journal of Research and Development on Public Policy, 2023)
City of Gastronomy as a field of science that studies food and culture is one of the focuses of Salatiga City to become one of the Culinary Creative Cities in the UCCN international event. In this case, the potential and diversity of social culture in Salatiga must be able to be utilized properly and maximally to achieve the goal of developing Salatiga City into a Gastronomic City. The Salatiga City Culture and Tourism Office through its main tasks and functions seeks to realize this. This study aims to determine the performance of the apparatus in the development of the Gastronomic City at the Culture and Tourism Office of the City of Salatiga, to determine the factors that hinder the development of the Gastronomic City and to determine the efforts made by the Culture and Tourism Office of Salatiga City in the development of the Gastronomic City. The research design used by the researcher is a qualitative research with a descriptive method and an inductive approach. Data collection techniques used are interviews, observation, and documentation. Furthermore, for data analysis techniques, researchers used data analysis techniques using the Miles and Huberman model which consisted of data collection, data reduction, data presentation, and drawing conclusions. The results of research based on the use of Performance Theory according to Agus Dwiyanto show that the performance of Apparatus in Gastronomic City Development can be said to be good in the dimensions of Productivity, Responsiveness, and Accountability and not good in the dimensions of Service Quality and Responsibility. There are several suggestions from the authors in this study for the need for maximum consistency and effort from the Culture and Tourism Office of Salatiga City so that the implementation of Gastronomy Development can be carried out optimally.